The association between Facebook addiction and depression: A pilot survey study among Bangladeshi students. (January 2019) - Mamun, M. A. Al; Griffiths, Mark D.
Highlights: Approximately 40% of Bangladeshi students were identified as being at risk of addiction to Facebook . There were no gender differences between males and females and the risk of Facebook addiction. Being single, having less involvement in physical activities, and sleep disturbance were risk factors for Facebook Addiction. Other risk factors for Facebook addiction were time spent on Facebook (≥5 h per day), and depression symptoms. Abstract: Social media addiction has become an area of increasing research interest over the past few years. However, there has been no previous research on social media addiction in Bangladesh. The present pilot study is the first ever in Bangladesh to examine the relationship between one specific form of social media addiction (i.e., ' Facebook addiction') and its associated predictors. This present study comprised 300 students from the University of Dhaka (Bangladesh) who participated in a survey that included questions relating to socio-demographics, health and behavioral measures, and the Bergen Facebook Addiction Scale (BFAS), and the nine-item Patient Health Questionnaire (PHQ9). The prevalence of FA was 39.7% (cutoff score was ≥18 on the BFAS). Using a regression analysis, the risk of being addicted to Facebook was predicted by being single, having less involvement in physical activities, sleep disturbance (more or less than 6 to 7 h of sleep), time spent on Facebook (≥5 h per day), and depression symptoms. Based on the sample in the present study, the risk of Facebook addiction (as assessed using the BFAS) appears to be a significant issue among Bangladeshi students, and depression to be one of the main comorbid factors.